Trends and progress in system identification - Eykhoff, Pieter, 1929- (IFAC series for graduates, research workers & practising engineers, 1981)
Trends and Progress in System Identification is a three-part book that focuses on model considerations, identification methods, and experimental conditions involved in system identification.